Gypsy homekeeping - Hamill, Ava (My University, 1892)
Introduction: Gypsies in all countries call themselves Rom which means husband- the idea being the nation and family blended in one. We cannot call the keeping of the Gypsy tent housekeeping; but call it Home-keeping, because we want to include not only the tent and surroundings, but the hearts of these people in their relations to home. The Gypsies are a virtue loving people- the very foundation for true home-keeping. The men are expected to be just as moral and virtuous as the women. Whenever a marriage takes places the contracting parties give a big feast which causes them to be poor for a long time afterwards. Verily, they are carrying out our idea that the best way to accumulate wealth is to be in debt. Marriage is sacred to them, and a Gypsy woman has never been known to desert her husband; and when the husband leaves the wife, she always thinks he will return to her, and does not think for a minute he has deserted her. There is a legend among them to the effect that when they left India, they were told never to dwell in houses, but always in tents; and they frequently quote from Scripture passages that say that they are to live in tents rather than in houses.
Citation: Hamill, Ava. Gypsy homekeeping. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Gypsy; Homekeeping; Tent; India; Marriage; Sociology; Theses; Manuscripts (documents)